Эпоха деятельности профессора Анджея Ситарского – расцвет познанской украинистики (воспоминание-посвящение как эго-текст) - Kosmeda, Tetyana (Studia Rossica Posnaniensia, 2021)
The paper is devoted to a holistic analysis of the scientific-organisational and scientific-didactic activity of the Head of the Institute of Russian and Ukrainian philology, Professor Andrzej Sitarski (2008–2019). In the paper, the author presents her reflections on the status of ego-texts along with their categories. The authorʹs attention is primarily focused on the evaluation of Professor Sitarski’s role in the upbringing of talented linguists, as well as on his personal contribution to the development of Poznań Ukrainian studies. The in-depth analysis is conducted on the basis of the category of memory that is depicted in ego-text genres, including the genre of memoirs-dedications. Professor Sitarski has an outstanding linguistic personality of a bilingual that boils down to particular verbal and nonverbal properties represented through his psychotype – his abilities of the elite linguistic character of a scientist and lecturer of Russian language are distinctive for him.